1962
DOI: 10.1192/bjp.108.454.274
|View full text |Cite
|
Sign up to set email alerts
|

A Factor Analysis of Some Child Psychiatric Clinic Data

Abstract: The Underwood Report (12) drew attention to the need for some system of classification in child psychiatry. This paper presents the results of a statistical study which was undertaken as relevant to that general enquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1965
1965
1993
1993

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…Baldwin (1948) reported that highly active pre-school cliildren later showed non-conformity and rebelliousness. Collins et al (1962) in a factoranalytic study of the records of children aged eight to ten who had attended the Maudsley children's department with symptoms not due to epilepsy, mental deficiency or psychosis, isolated factors of rebelliousness and anxiety in botli boys and girls, which may well be comparable. Follow-up studies from child guidance populations (Morris et al, 1956;Michael etal., 1957;O'Neil and Robins, 1958) have shown significant differences in outcome as regards mental health and criminality between the inhibited and acting-out groups of child guidance attenders, the latter faring much worse.…”
Section: Discussionmentioning
confidence: 99%
“…Baldwin (1948) reported that highly active pre-school cliildren later showed non-conformity and rebelliousness. Collins et al (1962) in a factoranalytic study of the records of children aged eight to ten who had attended the Maudsley children's department with symptoms not due to epilepsy, mental deficiency or psychosis, isolated factors of rebelliousness and anxiety in botli boys and girls, which may well be comparable. Follow-up studies from child guidance populations (Morris et al, 1956;Michael etal., 1957;O'Neil and Robins, 1958) have shown significant differences in outcome as regards mental health and criminality between the inhibited and acting-out groups of child guidance attenders, the latter faring much worse.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to economize on the number of traits to be assessed by including only one or two representatives of any cluster of highly correlated traits and as many representatives of independent factors as possible. Jenkins (1946Jenkins ( -1966 (cluster analysis) 500 Child guidance cases (about 9-15 yr) Collins, Maxwell and Cameron (1962) (factor analysis) Table 1 shows the results of three researches on problem behaviour in children. Jenkins (1946Jenkins ( , 1966 used cluster analysis and Collier, Maxwell and Cameron (1962) factor analysis on Child Guidance cases, while Phillips (1968) factor analysed items of "problem" bebaviour sbown among normal children.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the results of three researches on problem behaviour in children. Jenkins (1946Jenkins ( , 1966 used cluster analysis and Collier, Maxwell and Cameron (1962) factor analysis on Child Guidance cases, while Phillips (1968) factor analysed items of "problem" bebaviour sbown among normal children. Factors or clusters wbicb appear similar bave been arranged in horizontal rows in the table.…”
Section: Introductionmentioning
confidence: 99%
“…The terms are somewhat unfortunate in that there is no good reason to suppose that neurosis is much more closely related to personality than to antisocial behavior (Kanner, 1957). Nevertheless, although the terms may be somewhat misleading, the distinction between neurotic disorders and antisocial disorders has appeared in nearly all symptom cluster or factor analytic studies (Peterson, 1961;Collins et at., 1962;Eysenck and Rachman, 1965), and it has been argued that if symptoms tend to correlate or "go together" they should be classified together, [p. 164] In the present paper we will test the hypothesis that the magnitude of Factor I and II scores will vary systematically as a function of degree of emotional disturbanee. After having demonstrated the validity of the instruments, we will examine with what degree of efficiency the factor scores select disturbed children in a normal Day Care population and in selected reference groups of disturbed children.…”
mentioning
confidence: 99%